DIRECT ELECTROCHEMISTRY IN THE CHARACTERIZATION OF REDOX PROTEINS - NOVEL PROPERTIES OF AZOTOBACTER 7FE FERREDOXIN - Armstrong, F; George, S; Thomson, A; Yates, M (1988)
Fast diffusion-dominated electron transfer between Azotobacter chroococcum 7Fe ferredoxin, FdI, and pyrolytic graphite 'edge' electrodes, promoted by aminoglycosides, permits detailed voltammetric studies and preparation of oxidation states inaccessible by chemical titration. The [3Fe-4S] cluster exhibits pH dependent E 1 2 values (30°C); E 1 2 (alkaline) = 460 ± 10 mV vs NHE, -dE 1 2/d(pH) = 55 mV, pK = 7.8. The [4Fe-4S] cluster is characterised by an unusually low reduction potential, -645 ± 10 mV vs NHE, at pH 8.3, with a slight pH dependence, -dE 1 2/d(pH) ∼25 mV over the pH range 8.5-7.0. No redox couple is observed at potentials between -300 and +600 mV vs NHE. This shows that the [4Fe-4S] cluster is not an HIPIP-type centre. The electron paramagnetic resonance spectrum, centred at g = 1.93, of the product resulting from bulk electrolysis at -835 mV is assigned to a [4Fe-4S]+ cluster interacting magnetically with a reduced [3Fe-4S] cluster. © 1988.